KADAR CHOLINESTERASE DALAM DARAH PETANI DI DUSUN TAENO, KECAMATAN TELUK AMBON, KOTA AMBON - Samuel Titaley; Gracia Victoria Souisa (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
A vegetable farmer group in Taeno Hamlet, Teluk Ambon District, Ambon City uses pesticides in farming. Based on interviews with farmer extension agents, the use of pesticides in Taeno Hamlet was not in accordance with regulations. Farmers also do not realize the importance of using PPE when applying pesticides and do not understand the correct attitude / method when spraying. One indicator to monitor pesticide poisoning of farmers is blood cholinesterase testing. The purpose of this study was to determine the levels of Cholinesterase in the blood of farmers using pesticides in Taeno Hamlet, Teluk Ambon District, Ambon City. The research method used is descriptive experimental with laboratory testing. Cholinesterase examination will be carried out in Prodia's laboratory. The population in this study were 15 farmers in the